FEATURES OF PSYCHOLOGICAL AND PEDAGOGICAL TRAINING OF FUTURE SPECIALISTS IN HIGHER EDUCATIONAL INSTITUTIONS - Buhar, Anna; Pits, Iryna; Shevchuk, Kristina (Baltic Journal of Legal and Social Sciences, 2025)
Modern requirements for a higher education teacher have not only increased, but also changed radically. The new situation in society and the education system requires the training of a new type of teachers, capable of working e赏ectively and productively in constantly changing conditions. Now a teacher needs not only to have a high level of general culture, psychological and pedagogical competence, but also to take an unconventional approach to solving various psychological and pedagogical situations, to organize their own activities on a creative basis. It is generalized that psychological and pedagogical training of pedagogical personnel consists of a set of areas of psychological, theoretical and practical training, the main principles of which are a value-based attitude towards the subjects of the educational system, a focus on 蔞exibility and self- development; integration of fundamental and humanitarian professionally signi鶲cant knowledge; formation of skills to plan and implement the pedagogical process in accordance with the conditions of the educational system. The psychological and pedagogical competence of higher education applicants is considered as an integrative quality that re蔞ects the formation of a positive attitude towards education, the presence of formed scienti鶲c and theoretical, psychological and pedagogical, didactic and methodological knowledge and skills of their application in professional activity. It is concluded that in forming the content of professional training of pedagogical personnel, it is necessary to integrate fundamental training and professionally directed psychological and pedagogical training; to coordinate the goal of professional and pedagogical training of pedagogical personnel with the general goal of professional education; to ensure the unity of the main components of the training of pedagogical personnel (general cultural, psychological and pedagogical and subject-technical).
Keywords: psychological and pedagogical training, professional competence, pedagogical sta赏, subjects of the educational process of higher education institutions, professional activity.